Peningkatan Hasil Belajar Tingkat Tinggi Muatan Pembelajaran IPS Materi Makna Proklamasi Kemerdekaan Melalui Pembelajaran COVID-19 Metode Blended Learning pada Kelas VI UPTD SDN 01 Tanjuang Haro Sikabu-Kabu Pd. Panjang Semester Ganjil Tahun Pelajaran 2021 - Melya Kamera (Departement of Mathematics Education, 2022)
The purpose of this study was to describe the use of this study. The purpose of this study was to describe the use of Blended Learning Covid-19 learning methods to improve students' high-level learning outcomes in social studies learning content in class VI UPTD SDN 01 Tanjuang Haro Sikabu-Kabu Pd. Panjang. This type of research is Classroom Action Research. The research was carried out based on classroom action research steps with two cycles starting from the planning, implementation, observation, and reflection stages. The results of research data analysis show that the use of a scientific approach to the Blended Learning method can improve the ability of teachers to prepare high-level questions. This is evidenced by the acquisition of a score of 64.58 in the pre-cycle, increased to 72.91 in the first cycle, and increased to 89.58 in the second cycle. Furthermore, the results of the study of descriptions also experienced an increase, namely 64.10 in the pre-cycle increased to 76.92 in the first cycle of activities and increased to 87.71 in the second cycle. Furthermore, the learning outcomes of students' knowledge also increased, namely 68.07 in pre-cycle activities, increasing to 75.57 in the first cycle, increasing again to 81.61 in the second cycle with a large increase of 13.54. The learning outcomes of the skills aspect obtained an average of 66.34 in the pre-cycle, increasing to 76.15 in the first cycle and increasing again to 80.07 in the second cycle with a percentage increase of 13.73. Based on the results of this study, the conclusions of the research using the scientific approach of the Blended Learning method on the content of social studies learning need to be applied and developed in order to improve the quality of education.